Hospital Volume and Cardiac Complications of Endomyocardial Biopsy: A Retrospective Cohort Study of 9508 Adult Patients Using a Nationwide Inpatient Database in Japan - Isogai, Toshiaki (Clin Cardiol, 2015)
BACKGROUND: Recent research on complications with endomyocardial biopsy (EMB) has been based on single‐center or 2‐center studies in high‐volume cardiovascular centers. No study has examined the association between hospital volume and the complication rate after EMB. HYPOTHESIS: Hospital volume is inversely associated with cardiac complication rate after EMB. METHODS: Using the Diagnosis Procedure Combination database in Japan, we identified inpatients aged ≥20 years who underwent EMB under fluoroscopic guidance. We assessed cardiac complications requiring the following urgent procedures on the day of EMB or the day after: pericardiocentesis, surgical repair, and temporary pacing. RESULTS: Among 9508 eligible patients in 491 hospitals (male, 68%; mean age, 57.0 years), dilated cardiomyopathy was the most frequently diagnosed condition (35.4%). Twenty‐four patients (0.25%) required pericardiocentesis on the day of EMB. Three patients (0.03%) underwent surgical repair on the day of EMB or the day after. Sixty‐three patients (0.70%) required temporary pacing on the day of EMB. Higher hospital volume was associated with lower rates of pericardiocentesis (low volume, 0.4%; medium volume, 0.2%; high volume, 0.1%; P for the trend test, 0.019) and temporary pacing (low volume, 1.0%; medium volume, 0.7%; high volume, 0.2%; P for the trend test, < 0.001). In a multivariable logistic regression analysis, high hospital volume was significantly associated with a lower rate of the composite outcome of the procedures (reference, low volume; adjusted odds ratio, 0.22; 95% confidence interval, 0.08–0.62, P = 0.004). CONCLUSIONS: Serious cardiac complications of EMB were rare, but higher hospital volume was associated with lower complication rate.